Pseudo‐nitzschia arctica sp. nov., a new cold‐water cryptic Pseudo‐nitzschia species within the P. pseudodelicatissima complex. Issue 2 (8th March 2016) - Percopo, Isabella; Ruggiero, Maria Valeria; Balzano, Sergio; Gourvil, Priscillia; Lundholm, Nina; Siano, Raffaele; Tammilehto, Anna; Vaulot, Daniel; Sarno, Diana
Abstract : A new nontoxic Pseudo‐nitzschia species belonging to the P. pseudodelicatissima complex, P. arctica, was isolated from different areas of the Arctic. The erection of P. arctica is mainly supported by molecular data, since the species shares identical ultrastructure with another species in the complex, P. fryxelliana, and represents a new case of crypticity within the genus. Despite their morphological similarity, the two species are not closely related in phylogenies based on LSU, ITS and rbc L. Interestingly, P. arctica is phylogenetically most closely related to P. granii and P. subcurvata, from which the species is, however, morphologically different. P. granii and P. subcurvata lack the central larger interspace which is one of the defining features of the P. pseudodelicatissima complex. The close genetic relationship between P. arctica and the two species P. granii and P. subcurvata is demonstrated by analysis of the secondary structure of ITS2 which revealed no compensatory base changes, two hemi‐compensatory base changes, and two deletions in P. arctica with respect to the other two species. These findings emphasize that rates of morphological differentiation, molecular evolution and speciation are often incongruent for Pseudo‐nitzschia species, resulting in a restricted phylogenetic value for taxonomic characters used to discriminate species. The description of a new cryptic species, widely distributed in the Arctic and potentially representing an endemic component of the Arctic diatom flora, reinforces the idea of the existence of noncosmopolitan Pseudo‐nitzschia species and highlights the need for combined morphological and molecular analyses to assess the distributional patterns of phytoplankton species.